Vulnerability of municipal solid waste: An emerging threat to aquatic ecosystems. (January 2022) - Bhat, Rouf Ahmad; Singh, Dig Vijay; Qadri, Humaira; Dar, Gowhar Hamid; Dervash, Moonisa Aslam; Bhat, Shakeel Ahmad; Unal, Bengu Turkyilmaz; Ozturk, Munir; Hakeem, Khalid Rehman; Yousaf, Balal
Abstract: Dumping waste materials into aquatic ecosystems leads to pollution, which directly and indirectly poses a danger to all life forms. Currently, huge quantities of wastes are generated at a global scale with varying constituents, including organic fractions, emerging contaminants and toxic metals. These wastes release concentrated contaminants (leachates), which are lethal for all ecosystems around the globe because they contain varying concentrations of chemical constituents with BOD5 and COD in the order of 2 × 10 4 –2.7 × 10 4 mg/L, and 3.4 × 10 4 –3.8 × 10 4 mg/L, respectively. Herein, in-depth knowledge of municipal solid waste dumping into the aquatic ecosystems, changes in physicochemical characteristics, availability of in-/organic contaminants, and long-term unhealthy effects are presented. Moreover, an attempt has been made here to summarize the facts related to identifying the deadly impacts of waste on different ecosystem components. The unresolved challenges of municipal waste management are emphasized, which will help employ suitable waste management techniques and technologies to conserve the everlasting freshwater resources on earth. Highlights: Dumping waste materials into aquatic ecosystems poses a danger to all life forms. Deadly impacts of solid wastes on different ecosystem components are presented. MSW release concentrated contaminants, which are lethal for all ecosystems. Availability and long-term risks of contaminants from MSW are explained.